Microstructure evolution and hot deformation behavior of carbon nanotube reinforced 2009Al composite with bimodal grain structure. (20th April 2021) - Ma, K.; Liu, Z.Y.; Bi, S.; Zhang, X.X.; Xiao, B.L.; Ma, Z.Y.
Graphical abstract: Abstract: The hot deformation behaviors of the bimodal carbon nanotube reinforced 2009Al (CNT/2009Al) composite were studied by establishing processing map and characterizing the microstructure evolution. The results indicate that the grain size in the ultra-fine grained zones was stable during hot deformation, while the coarse grained zones were elongated with their long axis directions tending to be perpendicular to the compression direction. Low temperature with high strain rate (LTHR), as well as high temperature with low strain rate (HTLR) could increase the length/width ratio of the coarse grained zones. However, LTHR and HTLR could cause the instable deformation. The instable deformation at LTHR was induced by severe intragranular plastic deformation and the localized shear crack, while the instable deformation at HTLR resulted from the more deformation component at the coarse grained zones, and the micro-pore initiation due to CNT re-agglomeration at the boundaries between the coarse and the ultra-fine grained zones.